Optimization of Sequential Microwave-Ultrasonic-Assisted Extraction of Flavonoid Compounds from Moringa oleifera - Prasetyaningrum, Aji; Widayat, Widayat; Jos, Bakti; Ratnawati, Ratnawati; Riyanto, Teguh; Prinanda, Gian Restu; Le Monde, Brilliant Umara; Susanto, Evan Eduard (Trends in Sciences, 2022)
Flavonoid are bioactive compounds that can be found in moringa leaves. Extraction of bioactive compounds using conventional method requires a long time and low extract yields. This study was aimed to determine the optimum process conditions of sequential microwave-ultrasonic-assisted extraction (MUAE) of total flavonoids (TF) from moringa. The response surface methodology (RSM) with Box-Behnken design (BBD) was employed to determine the optimum operating conditions of MUAE among the set of variables: Time (10 - 30 min), temperature (40 - 60 °C), and solvent concentration (60 - 80%). Furthermore, the flavonoids content was determined using high-performance liquid chromatography (HPLC) and the antioxidant activity was analyzed using the DPPH scavenging method. The RSM optimization showed that the predicted optimum total flavonoids content was 3.25 quercetin equivalent (QE) mg/g, achieved under operating conditions at a temperature of 49.76 °C, extraction time 20.68 min and solvent concentration of 71.16 %. These optimum operating conditions were validated, resulting in an average error of 0.546 %. The MS/HPLC results showed that the content of quercetin and myricetin were 0.167 and 2.89 g/ 100 mL, respectively. Moringa extraction product has a strong antioxidant activity with IC50 of 74.58 - 74.62 µg/mL. HIGHLIGHTS For the first time, sequential microwave ultrasonic extraction of flavonoid components from moringa was conducted Data from the RSM method’s operating conditions optimization can be used to support the design of industrial-scale machines for extracting flavonoids In comparison to other extraction techniques, the flavonoid content obtained with sequential microwave-ultrasonic was the highest at 3.25 mg QE/g It was discovered that the antioxidant generated using sequential microwave-ultrasonic technology had a greater inhibitory power than the maceration approach, with an IC50 of 74.58 GRAPHICAL ABSTRACT